Randang Information Media Design As A Minangkabau Culinary Identity - Putri, Salsabila; Rahman, Fadlul; Ananta, Aryoni (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2024)
Culinary in Indonesia is very diverse, including randang, which comes from West Sumatra. Randang is a typical Minangkabau culinary identity known for its deliciousness. Randang has a complex cultural background. In the context of Minangkabau culture, the presentation of randang has a deep symbolic value and cannot be replaced by other dishes, so the term "Kapalo Samba" main course emerged. In the science of Visual Communication Design, the design of information media can be realized in the form of designing a user interface and user experience website. This work can be a solution according to the information that needs to be resolved. The processes carried out include data collection through interviews, literature studies, and questionnaires. The analysis uses the 5W + 1H method so that the Randang Minang Website information media design is created with a mix of design media. The results obtained for the design of Randang Minang information media in the form of a website are informative for desktop, tablet, and mobile versions. The media mix used for Randang Minang is in the form of posters, display stands, social media, x-banners, brochures, and merchandise. Write your abstract here.